The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1992
DOI: 10.1007/bf00204009
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of copper carbonates ? malachite Cu2(OH)2CO3 and azurite Cu3(OH)2(CO3)2

Abstract: Abstract. The thermodynamic properties of the copper carbonates malachite and azurite have been studied by adiabatic calorimetry, by heat-flux Calvet Calorimetry, by differential thermal analysis (DTA) and by thermogravimetric (TGA) analysis. The heat capacities, C o of natural malachite and azurite have been measured between 3.8 and 300 K by low-temperature adiabatic calorimetry. The heat capacity of azurite exhibits anomalous behavior at low temperatures. At 298.15 K the molar 8298.15 heat capacities C ~ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 17 publications
3
22
1
Order By: Relevance
“…In the temperature range (4 to 10.5) K we observed a small anomaly in the heat capacity of atacamite with a maximum at T = 8.6 K. A similar phenomenon was found for a synthetic sample at temperatures below 8 K by Kawaji et al (17) Recent studies (22) of the magnetic susceptibility of synthetic atacamite revealed the existence of a relaxation phenomenon below T = 8 K identical to that in spin glasses. We discovered anomalies in the heat capacities of other Cu-minerals such as azurite, (1) broshantite, (3) and dioptase. (4) We assumed these anomalies were connected with antiferromagnetic ordering of the magnetic moments of Cu 2 + ions as the temperature decreased.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the temperature range (4 to 10.5) K we observed a small anomaly in the heat capacity of atacamite with a maximum at T = 8.6 K. A similar phenomenon was found for a synthetic sample at temperatures below 8 K by Kawaji et al (17) Recent studies (22) of the magnetic susceptibility of synthetic atacamite revealed the existence of a relaxation phenomenon below T = 8 K identical to that in spin glasses. We discovered anomalies in the heat capacities of other Cu-minerals such as azurite, (1) broshantite, (3) and dioptase. (4) We assumed these anomalies were connected with antiferromagnetic ordering of the magnetic moments of Cu 2 + ions as the temperature decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Thermodynamic modelling allows one to determine the optimum parameters of oxidized mineral sulfurization in technical hydrothermal conditions and to establish the quantitative equilibrium composition of solid, liquid, and gaseous components of the system. We have performed thermodynamic modelling of the equilibrium composition in the hydrothermal systems of (oxidized copper mineral + sulfur + water) for Udocan copper deposits (1,2) on the basis of new thermodynamic data obtained by us earlier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Richardson and Brown (16) determined the standard enthalpy of formation of malachite by employing solution calorimetry in hydrochloric acid at T = 298.15 K. Kiseleva et al (17) obtained the standard enthalpies of formation of malachite and azurite from decomposition experiments in a drop calorimeter at T = 973 K. In addition, the standard entropies, S o m , of these minerals were derived from low-temperature measurements of the heat capacity by Kiseleva et al (17) Robie and Hemingway (18) (15) as well as Kiseleva et al (17) entered the thermodynamic database of Robie and Hemingway. (18) Using this data set, (18) the partial pressure of carbon dioxide for the equilibrium between malachite and tenorite (CuO) in an aqueous medium is predicted to be 0.32 MPa at T = 323.15 K. Applying the thermodynamic quantities given by Kiseleva et al (17) results in p(CO 2 ) = 5.20 MPa at T = 323.15 K. However, it will be shown in this work that tenorite can be transformed into pure malachite at p(CO 2 ) = 0.084 MPa and T = 323.15 K, which clearly disproves the prediction using the values listed in references 17 and 18. As the thermodynamic data for CuO are consistent with the JANAF tables (19) and are regarded to be fairly reliable, some of the literature values for the thermodynamic quantities of copper carbonates must be wrong.…”
Section: Introductionmentioning
confidence: 99%
“…Frost et al studied thermal decomposition of malachite and azurite by means of thermal, mass spectrometric, and infrared emission analyses and concluded that decomposition phenomenon occurred in six overlapping stages that dier in temperature [1]. Thermodynamic properties of copper carbonates were studied by Kiseleva et al [9] and thermogravimetry of mechanically activated malachite and physical mixture of malachite and calcite were studied by Wieczorek-Ciurowa et al [10] to illuminate the mechanism for further process. Nowadays malachite have been although still used for production of copper, in ancient time it was used as pigments in manuscripts, glasses and glaze [1].…”
Section: Introductionmentioning
confidence: 99%